1989
DOI: 10.1021/j100349a059
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state of mixtures of simple molecular fluids: the carbon disulfide + dichloromethane system

Abstract: The equation of state of CS2 + CH2C12 has been studied over the whole composition range and for 298.15 < T/K < 319.15 and 0.1 < p/MPa < 40.0. The results indicate that the system shows a higher degree of nonideality than CS2 + CC14, as well as larger pressure dependences of GE, Vs, and TSE. While the Gubbins-Gray perturbation theory leads to conclusions in agreement with the data, the Deiters equation of state gives worse results than for CS2 + CC14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

1991
1991
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…Even though the value (n) =21 obtained for CF4 agrees quite well with that used in ref 3, and with the one obtained by Compostizo et al (24), the small value obtained for CHF3 is Table XIV. Thermal Expansion Coefficient ( '1 K"1) for Trifluoromethane at Various Pressures (P, har) and Temperatures (T, K)…”
Section: Monatomic Fluid Modelsupporting
confidence: 90%
See 2 more Smart Citations
“…Even though the value (n) =21 obtained for CF4 agrees quite well with that used in ref 3, and with the one obtained by Compostizo et al (24), the small value obtained for CHF3 is Table XIV. Thermal Expansion Coefficient ( '1 K"1) for Trifluoromethane at Various Pressures (P, har) and Temperatures (T, K)…”
Section: Monatomic Fluid Modelsupporting
confidence: 90%
“…As previously (24), the starting point Is the assumption of an effective intermolecular potential of the form U^r,T,V)…”
Section: Monatomic Fluid Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The densitometer was calibrated with different substances of well-known densities. 6 In contrast to previous works22"24 we have found that a linear relationship between the density and the square of the period of vibration r is not suitable for obtaining the highest precision. Even though, theoretically, one might expect a r4 correction term, we have found that a r-1 term gives better results.…”
Section: Methodscontrasting
confidence: 74%
“…Even though, theoretically, one might expect a r4 correction term, we have found that a r-1 term gives better results. We have used p-p-T data reported in the literature for N2,25 CO2,26 and the substances studied in ref 6 for establishing a calibration curve for the vibrating tube. The calibration curve was tested after the experiments on each pure substance were carried out.…”
Section: Methodsmentioning
confidence: 99%